Capillaroscopy in Systemic Autoimmune Rheumatic Diseases: A Clinical Tool Linking Diagnosis and Pathogenesis (Canadian Rheumatology Today, 2025)
Systemic autoimmune rheumatic diseases (SARDs) including systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and idiopathic inflammatory myopathies (IIMs) are multisystemic, potentially life-threatening autoimmune diseases. These diseases are associated with the highest frequency of disease-associated morbidity and mortality among rheumatic diseases, largely because their complex pathophysiology remains poorly and incompletely understood. Mortality in SARDs is associated with profound vascular dysfunction ranging from cardiovascular disease to more discreet localized vascular complications including Raynaud’s phenomenon (RP), digital ulcers, and pulmonary arterial hypertension (PAH). These vascular complications stem from damage to endothelial cells caused by immune complex deposition, platelet activation, autoantibodies that promote thrombosis (e.g., antiphospholipid antibodies), and immune dysregulation.The relationship between endothelial cell dysfunction and SARDs was first recognized by Maurice Raynaud in the 19th-century, particularly in the context of localized digital ischemia and gangrene. RP is a frequently-encountered problem in clinical practice, with a prevalence in the general population ranging from approximately 5–18%. While most cases of RP are not associated with SARDs, patients with SARDs commonly experience RP. This underscores the importance of vasculopathy related to endothelial dysfunction in the pathogenesis of SARDs.RP is often the earliest presenting feature in up to 20% of patients with SARDs. Indeed, greater than 95% of patients with SSc experience RP.11 Patients with SLE, IIMs including anti‑synthetase syndrome (ASyS), and Sjögren’s disease are also commonly affected. Hence, a closer evaluation for microvascular changes is paramount in the clinical assessment of patients with SARDs. This article will review how nailfold video capillaroscopy is emerging as a valuable point-of-care tool for diagnosis and risk stratification by providing a window into the underlying endothelial dysfunction observed in these conditions.